Métodos e recursos para ensinar matemática nos anos iniciais do ensino fundamental - SOUZA, Érica Tatiana Noronha de (2018)
The present Work of Conclusion of Course (TCC) approaches the thematic of the methods and resources used for the teaching of mathematics in the initial years of Elementary School, highlighting the conceptions and tendencies that involve them. It aims to show the methodologies and resources for teaching mathematics in this stage of schooling, making it necessary to approach the mathematical contents, methods and resources adopted by the teaching network. The work was based first on a bibliographical survey of some authors who served as theoretical references to give a foundation in the discussion of the theme. In the second moment, a data collection was carried out, having as subjects of the research two teachers of the initial years of the Elementary School of the public school system. The results showed an improvement in the teaching of mathematics in the referred phase of schooling of the teachers with the introduction of the methods and resources adopted. It is concluded that the choice of them is not as simple as it seems at first. Mathematics education needs to take into account its target audience to more broadly identify the specificities of each level of schooling for children, enabling them to develop their cognitive abilities.